Float like a butterfly [videorecording (DVD)] - Winters, Carmel; Fay, Hilda; Roddy, Lalor; O'Hare, Aiden; Doupe, Hazel; Devaney, Dara; Collins, Johnny (Level 33 Entertainment, 2020)
In this powerful and timely story of a girl's pursuit of freedom and belonging, fifteen-year-old Frances fights for her humble Irish community by becoming a boxer like her idol, Muhammad Ali. While society may be determined to break her spirit and destroy her way of life, Frances was not born to be broken. Instead, she digs deep to prove to her disillusioned father that she's a true champion.